2010
DOI: 10.3390/s100403180
|View full text |Cite
|
Sign up to set email alerts
|

A New Myohaptic Instrument to Assess Wrist Motion Dynamically

Abstract: The pathophysiological assessment of joint properties and voluntary motion in neurological patients remains a challenge. This is typically the case in cerebellar patients, who exhibit dysmetric movements due to the dysfunction of cerebellar circuitry. Several tools have been developed, but so far most of these tools have remained confined to laboratories, with a lack of standardization. We report on a new device which combines the use of electromyographic (EMG) sensors with haptic technology for the dynamic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Indeed, hypermetria is larger when inertial loads are added to the moving hand, as a consequence of the inability to adequately tune the intensity of the antagonist activity. Cerebellar patients may also show impairments in the adaptation to external damping during fast reversal movements [133]. Dysmetria may be associated with a kinetic tremor, which predominates in visually guided tasks performed at slow or moderate velocities.…”
Section: Dysfunction Of Voluntary Limb Movements In Cerebellar Patienmentioning
confidence: 99%
“…Indeed, hypermetria is larger when inertial loads are added to the moving hand, as a consequence of the inability to adequately tune the intensity of the antagonist activity. Cerebellar patients may also show impairments in the adaptation to external damping during fast reversal movements [133]. Dysmetria may be associated with a kinetic tremor, which predominates in visually guided tasks performed at slow or moderate velocities.…”
Section: Dysfunction Of Voluntary Limb Movements In Cerebellar Patienmentioning
confidence: 99%
“…The cerebellum would estimate and predict the movement dynamics of the body and inform the cerebral cortex in particular via the dentato-thalamo-cortical circuit [150]. The difficulties of cerebellar patients to adapt to changes in the damping of the joints also argue for such a predictive role [151].…”
Section: Mario Manto Hiroshi Mitomamentioning
confidence: 99%
“…EMG studies have shown delayed onset latencies of antagonist activities [68], abnormal rates of rise of agonist/antagonist EMG activities [100] and impaired adaptation to mechanical conditions such as increased inertia or damping [107]. The agonist EMG activity is characterized by smaller magnitudes (smaller torques to generate a launching force) and prolonged duration [68, 100].…”
Section: Cerebellar Dysmetria (Florian Bodranghien and Mario Manto)mentioning
confidence: 99%